Introduction of Reliance Jio and Telecom Stock Returns : A Test of Competition Hypothesis in the Bombay Stock Exchange - Ganesamoorthy, L.; Anbazhagan, K. (Indian Journal of Research in Capital Markets, 2016)
The telecommunication sector is one of the fast-developing sectors in India. Hence, many investors like to invest in telecommunication companies. This sector has been experiencing big events during the current decade such as 2G spectrum auction and scams, 3G and 4G spectrum allocations, etc. On September 1, 2016, a big business concern, Reliance Industries Ltd. introduced their new-product Reliance Jio network services through their subsidiary company with attractive offers both for voice call and 4G Internet mobile services. It threatened other mobile service providers who want to retain their market share. The study analyzed the impact of the event on the telecommunication sector in India using standard event study methodology. The study found that the telecommunication sector in India was affected by the introduction of Jio services as shown by returns on BSE Telecom index (-5.67%). There was a significant impact on sample companies (listed mobile network service providers). On the date of the event, the average abnormal returns was -6.695%. It was also seen that there was a significant sustaining impact on sample companies in the market as shown by the results of CAR. Among the sample companies, Idea Cellular Ltd. was affected severely by the event followed by Reliance Communications Ltd., but there was severe sustaining effect of the event on the abnormal returns of Idea Cellular Ltd. followed by that of Bharti Airtel Ltd.